SAA3 deficiency exacerbates intestinal fibrosis in DSS-induced IBD mouse model - Xiaodong Zou; Tong Wu; Jianjiao Lin; Tao Su; Hui Xiao; Chuyan Ni; Lijuan Hu; Wenchu Lin; Weilin Chen; Richard D. Ye; Li Xiang (Cell Death Discovery)
Abstract Intestinal fibrosis, as a late-stage complication of inflammatory bowel disease (IBD), leads to bowel obstruction and requires surgical intervention, significantly lowering the quality of life of affected patients. SAA3, a highly conserved member of the serum amyloid A (SAA) apolipoprotein family in mice, is synthesized primarily as an acute phase reactant in response to infection, inflammation and trauma. An increasing number of evidence suggests that SAA3 exerts a vital role in the fibrotic process, even though the underlying mechanisms are not yet fully comprehended. This study utilized dextran sulfate sodium (DSS) to establish an IBD mouse model and observed that the SAA3-deficient mice exhibited more severe intestinal fibrosis. Our results further indicated that SAA3 genetic disruption in fibroblasts enhanced cell activation to myofibroblasts through HSPB1/NF-κB/TGF-β1/Smads signaling cascade, exacerbating the pathological phenotype of intestinal fibrosis. Collectively, our results shed novel lights on regulating SAA3 in intestinal fibrosis and indicate the potential to develop therapeutic strategies for IBD patients.